EMPREGO DOMÉSTICO: Revendo o Novo - Britto da Motta, Alda (Caderno CRH, 2007)
Considerando o novo como culminância ou momento privilegiado de uma processo, o artigo aponta alguns momentos de mudança do trabalho doméstico na História: de produção coletiva a individual, de não-remunerada a assalariada, exercida diferencialmente segundo gêneros, classes e gerações. Contemporaneamente, enfim legitimado como análise acadêmica, realiza-se em um contexto social de crise, onde tanto mulheres como classes populares se demonstram capazes de ação política. Based on the definition that the "new" in given social process are those moments in which qualification changes take place, this article discusses domestic work in History. It focuses on change from collective to individualized production and from unpaid to wage labor; and also on how it has been differentiated on the basis of the workers’ sex, class and generation. The article focuses basically on the new trends in the condition of housemaids and servants in Brazil, who are begining to organize for political action. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br